2000
DOI: 10.1093/jn/130.6.1578
|View full text |Cite
|
Sign up to set email alerts
|

Fruits and Vegetables Increase Plasma Carotenoids and Vitamins and Decrease Homocysteine in Humans

Abstract: Observational epidemiologic studies have shown that a high consumption of fruits and vegetables is associated with a decreased risk of chronic diseases. Little is known about the bioavailability of constituents from vegetables and fruits and the effect of these constituents on markers for disease risk. Currently, the recommendation is to increase intake of a mix of fruits and vegetables ("five a day"). We investigated the effect of this recommendation on plasma carotenoids, vitamins and homocysteine concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
4
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(110 citation statements)
references
References 30 publications
6
93
4
7
Order By: Relevance
“…Our findings are in accordance with two other published intervention studies that have used mixed fruit and vegetable diets Broekmans et al, 2000), although a direct comparison may be hampered by focus on different research questions and different length of interventions. The differences in the magnitude of relative response observed in the three studies could be explained by the difference in amounts and type of fruits and vegetables included in the high and low diets of these studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are in accordance with two other published intervention studies that have used mixed fruit and vegetable diets Broekmans et al, 2000), although a direct comparison may be hampered by focus on different research questions and different length of interventions. The differences in the magnitude of relative response observed in the three studies could be explained by the difference in amounts and type of fruits and vegetables included in the high and low diets of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of carotenoid intake between the low and the high diet varied between the three studies. As an example, in the study by Broekmans et al (2000) the high diet contained 4.9 times more a-carotene than the low diet, whereas in the present study the difference in a-carotene content between the high and low diet was 2.5 times. The relative differences for b-carotene intake are similar in the three studies, and this is probably because b-carotene is present in a greater range of vegetables than a-carotene.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Mean estimated folic acid intake also significantly increased in weeks 3-6. Deficiency of this nutrient has been linked to hyperhomocysteinaemia, an independent risk factor for coronary heart disease (Broekmans et al, 2000). Increased intakes of fruit and vegetables have been shown to decrease plasma homocysteine concentration although this was not measured in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…However, as fruit consumption decreased, the effect of coffee on homocysteine became significant even when lower quantities of coffee were consumed (Table 4). It has been suggested that at least 5 servings of fruits and vegetables a day are necessary in order to observe a decrease in homocysteine levels, 15,16 and this agrees with our findings. It has been suggested that this protective effect of fruit against the homocysteine-raising effect of coffee could be due to folic acid that may affect the homocysteine concentration.…”
Section: Discussionsupporting
confidence: 93%